Diversification of forest management can mitigate wind damage risk and maintain biodiversity - Potterf, Mária; Eyvindson, Kyle; Blattert, Clemens; Triviño, María; Burner, Ryan C.; Burgas, Daniel; Mönkkönen, Mikko (Springer Science and Business Media LLC, 2023)
Mitigating future forest risks, safeguarding timber revenues and improving biodiversity are key considerations for current boreal forest management. Alternatives to rotation forestry likely have an important role, but how they will perform under a changing climate remains unclear. We used a boreal forest growth simulator to explore how variations on traditional clear-cutting, in rotation length, thinning intensity, and increasing number of remaining trees after final harvest (green tree retention), and on extent of continuous cover forestry will affect stand-level probability of wind damage, timber production, deadwood volume, and habitats for forest species. We used business-as-usual rotation forestry as a baseline and compared alternative management adaptations under the reference and two climate change scenarios. Climate change increased overall timber production and had lower impacts on biodiversity compared to management adaptations. Shortening the rotation length reduced the probability of wind damage compared to business-as-usual, but also decreased both deadwood volume and suitable habitats for our focal species. Continuous cover forestry, and management with refraining from thinnings, and extension of rotation length represent complementary approaches benefiting biodiversity, with respective effects of improving timber revenues, reducing wind damage risk, and benefiting old-growth forest structures. However, extensive application of rotation length shortening to mitigate wind damage risk may be detrimental for forest biodiversity. To safeguard forest biodiversity over the landscape, shortening of the rotation length could be complemented with widespread application of regimes promoting old-growth forest structures.
Keywords: Boreal forests; Continuous cover forestry; Climate change; Forest management planning; Forest modeling; Habitat suitability index; Rotation forestry